Influence of Crystallinity of Lithium Thiophosphate Solid Electrolytes on the Performance of Solid‐State Batteries. Issue 24 (6th May 2021) - Wang, Shuo; Zhang, Wenbo; Chen, Xiang; Das, Dyuman; Ruess, Raffael; Gautam, Ajay; Walther, Felix; Ohno, Saneyuki; Koerver, Raimund; Zhang, Qiang; Zeier, Wolfgang G.; Richter, Felix H.; et al.
Abstract: Solid electrolytes (SEs) largely define the properties of all‐solid‐state batteries (ASSBs) and are expected to improve their safety, stability, and performance. Their ionic conductivity has much improved in recent years, enabling higher power and energy density. However, more subtle parameters, such as crystallinity, may also influence the electrochemical performance of cells. In this work, the correlation between the performance of ASSBs and thiophosphate SEs having the same stoichiometry, but different crystallinity is investigated. In In/InLi | SE | LiCoO2 @ LiNb0.5 Ta0.5 O3 model cells, better cycling and rate performance is achieved when using glass/glass‐ceramic SEs (e.g., 75Li2 S·25P2 S5 glass, 70Li2 S·30P2 S5 glass, and Li6 PS5 Cl glass‐ceramic). This can be mostly attributed to the mitigation of contact loss by the glass/glass‐ceramic SEs compared to their crystalline SE counterparts. Furthermore, the SE decomposition at typical cathode potentials is investigated by using SE and carbon composites as cathodes. Larger volume changes and more severe decomposition are observed with crystalline SEs in the SE/carbon composite cathode after cycling. The crystalline SEs show higher electronic partial conductivity which results in more degradation in the composite cathode. This work sheds light on optimized composite cathode design for ASSB by carefully choosing solid electrolytes with appropriate mechanical and (electro‐)chemical properties. Abstract : The influence of sulfide solid electrolytes (SEs) with the same stoichiometry but different crystallinity on the performance of ASSBs is systematically studied. Using In/InLi | SE | LiCoO2 @LiNb0.5 Ta0.5 O3 as a model battery, glass/glass‐ceramic SE shows better electrochemical performance than its counterparts, crystalline SEs. This is mainly due to the reduced contact loss in the composite cathode with glass/glass‐ceramic SEs.